Solve the following system using elimination:
{5 x = 4 y + 8 | (equation 1)
{3 y = 3 x - 3 | (equation 2)
Express the system in standard form:
{5 x - 4 y = 8 | (equation 1)
{-(3 x) + 3 y = -3 | (equation 2)
Add 3/5 × (equation 1) to equation 2:
{5 x - 4 y = 8 | (equation 1)
{0 x+(3 y)/5 = 9/5 | (equation 2)
Multiply equation 2 by 5/3:
{5 x - 4 y = 8 | (equation 1)
{0 x+y = 3 | (equation 2)
Add 4 × (equation 2) to equation 1:
{5 x+0 y = 20 | (equation 1)
{0 x+y = 3 | (equation 2)
Divide equation 1 by 5:
{x+0 y = 4 | (equation 1)
{0 x+y = 3 | (equation 2)
Collect results:
Answer: {x = 4
{y = 3